EVALUASI PELAKSANAAN PROGRAM BANTUAN LANGSUNG TUNAI DANA DESA (BLTDD) DI DESA RASAU JAYA UMUM - Jeprianus, Jeprianus; Arkanudin, Arkanudin; Alamri, Annisa Rizqa; Gafar, Zakiah Hasan; Maya, Maya; Riyanto, Riyanto; Deni, Deni (FISIP Universitas Tanjungpura, 2023)
This research aims to evaluate the implementation process of the Village Fund Direct Cash Assistance Program, starting from the recruitment process to the distribution of BLTDD assistance in Rasau Jaya General Village. This research uses evaluation theory according to William N Dunn in Syahriza Rizani, F. (2023) which states that this evaluation model is a focused approach to evaluation values that considers facts with a present and past orientation so as to give rise to a recommendation with 6 parameters namely, Effectiveness, Efficiency, Adequacy, Alignment, Responsiveness and Accuracy. This research uses a qualitative descriptive method, namely a research method that focuses on explanation, interpretation and understanding of phenomena. The data collection techniques used in this research were observation, interviews and documentation. The results of this research found that Rasau Jaya General Village is the only one that uses the Village Fund Direct Cash Assistance (BLTDD) fund distribution system which is carried out by distributing the Cash Management System (CMS), which is a type of financial management service aimed at non-retail customers. So you can manage your finances directly through online facilities. Rasau Jaya Village is the first pilot in Indonesia to operate fund distribution using a Cash Management System (CMS). The targets of this research are people who have many children, high levels of stunting and the elderly as well as people who have been ill for years so they have lost their livelihoods and have no income to meet basic needs in their daily lives.